Malignant fibrous histiocytoma of the mediastinum. Issue 770 (December 1989) - Aggarwal, P.; Sharma, S. K.; Dey, A. B.; Chattopadhyay, T. K.; Mathur, M.
Abstract : A case of malignant fibrous histiocytoma of the mediastinum presenting with unusual features of fever and leucocytosis is reported. This is the youngest patient reported in the literature who had this tumour in the mediastinum.